The Experience of Breastfeeding Mothers with LBW in NICU - Elsy juni andri kariny; Herlin Fitriani Kurniawati; Andari Wuri Astuti (Universitas 'Aisyiyah Yogyakarta, 2021)
More than 80% of premature infants are born between 32-37 weeks of age have low birth weight and die due to lack of care, such as breastfeeding which LBW urgently needs. Neonatal Intensive Care Unit (NICU) is the main place to deal with LBW which provides the needed care such as information on LBW care and optimal nutrition by breastfeeding. Scoping review is to describe The Experience of Breastfeeding Mothers with Low Birth Weight in NICU. The method used is consists of 6 stages, namely identifying questions with the PEOS Framework, identifying relevant studies, selecting studies using inclusion and exclusion criteria, conducting critical-appraisals to assess the quality of literature, performing data extraction, PRISMA Flowchart. 12 selected literatures with good quality. Five themes are emerged from the results namely factors affecting breastfeeding, barriers to breastfeeding, impact, and the support that should be given. LBW makes a lack of milk production so that the mother experiences stress, depression, disappointment, anxiety and fatigue. The Lack of support from health workers which still makes mothers confused about proper baby care. So that the success of breastfeeding at LBW on average is less than optimal. There is a need for further research on the effect of psychological support by health workers in the achievement of breastfeeding success in NICU-based LBW